Challenging Virtual Rigidity: Gatekeeping and Organizational Communication of a Remote Housewives Editorial Team in Small Publishing - Dian Istiaty; Tria Patrianti (Jogjakarta Communication Conference (JCC), 2026)
Traditional organizational communication theories often characterize virtual workspaces as rigid and limited in building team chemistry. However, this study challenges that assumption by exploring the organizational communication dynamics of Forsenbooks, a small, independent publisher in Indonesia operated entirely by a remote editorial team consisting of six housewives. This research aims to investigate how these women negotiate their dual roles as domestic caretakers and professional gatekeepers in a virtual environment. Utilizing a qualitative case study method, data were gathered through participant observation and in-depth interviews. This paper uses Gatekeeping theory and the Computer-Mediated Communication (CMC) perspective as its primary analytical framework. The findings reveal that this team successfully dismantles the limitations of virtual communication. They achieve this by developing an adaptive internal communication strategy, fostering strong chemistry through text-based interactions while maintaining rigorous editorial standards via online platforms. Ultimately, this study concludes that such virtual gatekeeping practices not only ensure business sustainability but also serve as a driving agent for digital literacy and the socio-economic empowerment of housewives in the modern creative industry.